THE EFFECT OF EMOTIONAL INTELLIGENCE ON EMPLOYEE ENGAGEMENT WITH WORK LIFE-BALANCE AS AN INTERVENING VARIABLE (CASE STUDY OF A COFFEE SHOP IN PEKANBARU) - Mulkidatul Alchaer; Hafidzah Nurjannah (Jurnal Apresiasi Ekonomi, 2025)
This study aims to determine the effect of emotional intelligence on employee engagement with work-life balance as an intervening variable (case study of coffee shops in Pekanbaru). The population in this study were all employees who work in coffee shops in Pekanbaru city with an unlimited number. The sampling technique in this study used a non-probability sampling method through purposive probability sampling totaling 100 people. The descriptive analysis used in this study is quantitative descriptive analysis and SmartPLS Software. PLS (Partial Least Square). The results of this study indicate that emotional intelligence has a positive and significant effect on employee engagement through work-life balance.Keywords:Emotional Intelligence, Employee engagement, Work-life balance